Event-Triggered Time-Varying Formation Tracking Control for Multi-Agent Systems with a Switching-Directed Topology - Xiaoya Chen; Huiying Chen (Mathematics, 2023)
This study investigates the problem of time-varying formation tracking (TVFT) control involving event-triggered and switching topological mechanisms. Specifically, TVFT is evaluated with a consensus analysis and deduced via the use of linear matrix inequality techniques combined with Lyapunov stability theory. This strategy obtains sufficient conditions for system stability and the feedback and coupling gains. In addition, the TVFT compensational signals are presented in two cases to enhance the algorithm’s applicability. Given that ideal multi-agent systems (MASs) should be highly flexible and resilient, we propose a co-design algorithm that strikes a balance between the need for a lower communication frequency and a reduction in the state disagreements of agents. Finally, the effectiveness of the theoretical analysis is demonstrated through 3D figures and comparison tables, from which it can be concluded that the communication frequency of the MAS was clearly reduced on the basis of ensuring consensus performance via applying the algorithm proposed in this paper.